Evolução da perda de peso entre indivíduos da fila de espera para a cirurgia bariátrica em um ambulatório multidisciplinar de atenção secundária à saúde - Gushiken, Cintia Satie [UNESP]; Vulcano, Daniela Salate Biagioni [UNESP]; Tardivo, Ana Paula [UNESP]; Rasera Jr., Irineu [UNESP]; Leite, Celso Vieira de Souza [UNESP]; De Oliveira, Maria Rita Marques [UNESP] (My University, 2010)
Objective: The objective of this study is to characterize the assistance and analyze patient's adherence to nutritional follow-up while in the waiting line for bariatric surgery in a multidisciplinary, secondary healthcare outpatient clinic. Methods: This retrospective study was based on the nutritional records of 59 patients subjected to bariatric surgery at the Hospital das Clinics de Botucatu, from 2001 to 2008. The population studied was distributed into 8 groups and analyzed according to follow-up duration. The analysis took into account the evolution of body weight and the number of follow-up visits in a given period. The Kruskal-Wallis test was used to compare data between groups while Spearman's coefficient was used to test correlations. Results: Among the 59 studied patients, 42 (71.2%) returned to the clinic at least once in six months. Of these, 67.8% lost weight while in the waiting line and 27.1% of them lost more than 10% of their body weight. The greatest weight losses in the preoperative period were found in the groups that had more than six months of nutrition follow-up. There was a mean delay of three months between return visits, which could have contributed to the low adherence to follow-up. Conclusion: The patients in the waiting line for surgery analyzed in this study presented low adherence to the long-spaced return visits. The greatest weight losses were observed in groups that had been followed for more than six months. This shows that, to achieve the desired weight loss and an adequate education process before surgery, at least six months of follow-up and regular visits are necessary.
Evolution of weight loss among individuals in the waiting line for bariatric surgery in a multidisciplinary secondary healthcare outpatient clinic
Keywords: Ambulatory care; Bariatric surgery; Morbid; Nutrition education; Obesity; bariatric surgery; body weight; correlation analysis; correlation coefficient; follow up; health care facility; health service; hospital admission; human; Kruskal Wallis test; major clinical study; nutritional assessment; outpatient department; patient; patient compliance; preoperative period; retrospective study; weight reduction